2022
DOI: 10.3390/polym14163232
|View full text |Cite
|
Sign up to set email alerts
|

Active Thermoplastic Starch Film with Watermelon Rind Extract for Future Biodegradable Food Packaging

Abstract: Petrochemical plastic wastes generate serious environmental problems because they are resistant to natural decomposition. The aim of this study was to develop a biodegradable active thermoplastic film composed of polyvinyl alcohol (PVA), corn starch (ST), glycerol, and the active compounds from watermelon rind extract (WMRE), or PVA/ST/WMRE, using the casting technique. The film was examined for its mechanical, antioxidant, and functional properties against selected foodborne pathogens. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This can be caused by the H-bonding formation between compounds from the extract with TPS. This H-bond crosslinking can also be responsible for changes in mechanical properties (higher TS and YM) [ 34 ]. Fingerprint peaks for the polysaccharide are in the range of 1200–900 cm −1 and are assigned to stretching C-O and C-C bonds as well as bending C-O-H groups from anhydroglucoside units of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…This can be caused by the H-bonding formation between compounds from the extract with TPS. This H-bond crosslinking can also be responsible for changes in mechanical properties (higher TS and YM) [ 34 ]. Fingerprint peaks for the polysaccharide are in the range of 1200–900 cm −1 and are assigned to stretching C-O and C-C bonds as well as bending C-O-H groups from anhydroglucoside units of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…According to Charles et al [ 8 ], potato peel starch can be used in the packaging of chilled and frozen foods. Meanwhile, Thodanakasem et al [ 9 ] used watermelon rind. Morphological structure, mechanical properties, thermal properties, barrier properties, and biodegradability were considered the standard characterization techniques for obtaining a high-quality starch-based film [ 1 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of novel and biodegradable materials from renewable sources for different applications is the focus of scientific attention, primarily due to the raised awareness on the environmental impact of petroleum-based plastics, especially in the context of water, soil, and air pollution, as well as the increased omnipresence of microplastics [ 1 , 2 , 3 ]. It was shown that one of the promising alternatives to petroleum-based packaging plastics is starch due to its biodegradability, availability, renewability, and low cost [ 3 , 4 , 5 ]. Starch-based materials such as thermoplastic starch (TPS), with or without the addition of other biodegradable polymers, can be processed employing conventional equipment for the production of traditional thermoplastic materials and transformed by injection or blow molding into the final products suitable for food packaging [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This relates to packages containing additives that maintain or extend food quality or shelf-life and therefore contribute to the reduction in spoilage, food waste, food recalls, and foodborne illness outbreaks [ 10 ]. There are several reports on the preparation of TPS-based materials with bioactive components by conventional methods for the development of active food packaging [ 4 , 7 , 8 , 11 , 12 ]. These reports include the addition of watermelon rind extract to a water solution at 70 °C before solvent casting [ 4 ], the incorporation of TiO 2 nanoparticles by extrusion at 165 °C [ 7 ], and the addition of copper particles by thermocompression at 140 °C [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation